Pregnancy outcome in a rare case of complex cyanotic congenital heart disease - Kamat, Amitha V.; Kittur, Sahaja S.; Hiremath, Mallikarjun G.; Murthy, S. R. Chandana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
A 28 year old primigravida with the very rare congenital heart condition of single ventricle with single atrium presented with 34 weeks gestation, and underwent caesarean section with minimal morbidity. As the condition is not known for survival into adulthood, the carrying of a pregnancy successfully to near term makes this an even rarer case.